Slated for death - Duncan, Elizabeth J. (Duncan, Elizabeth J. Penny Brannigan mystery., 2015)
"When the body of well-liked and respectable Glenda Roberts is discovered at the bottom of a former slate mine--now a busy tourist attraction--pandemonium erupts in the North Wales town of Llanelen. Penny Brannigan finds herself drawn into the investigation when jars of her house-brand hand cream are found among counterfeit inventory Glenda and her sister were selling. Police are convinced that the mine operator --whose asthmatic son suffered an almost-fatal attack due to the merchandise--is responsible for Glenda's death. But Penny's not so sure" --